Titch - Hutchins, Pat, 1942- (Aladdin Books ; Maxwell Macmillan Canada ; Maxwell Macmillan International, 1993)
Titch feels left out because he is so much smaller than his brother and sister until he gets a little seed that grows bigger than anything they have.